Analysis of Strategic Plan Forms for Educational Units: Literature Review and Institutional Analysis - Shelty D. M Sumual; Joulanda A.M. Rawis; Jeffry S.J. Lengkong; Eugeni Sumanti; Salam Surbakti (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Strategic planning in education units is an important instrument in ensuring adaptive, effective, and sustainable management of institutions in the midst of the complexity of global change. This study aims to analyze the form and structure of strategic plans used by various educational institutions, as well as evaluate the key elements that influence their effectiveness in achieving institutional objectives. A qualitative approach with the literature study method was used to review more than twenty strategic plan documents from primary, secondary, and tertiary education institutions. The analysis is carried out through thematic classification and mapping of strategic components such as vision-mission, SWOT analysis, strategic objectives, performance indicators, and monitoring-evaluation systems. The results show that the similarity of document structures does not always guarantee the effectiveness of implementation, as success is strongly influenced by the quality of leadership, stakeholder participation, and the linkage between planning and budgeting. Other findings reveal that a participatory, data-driven, and integrative approach to performance management systems is a determinant factor for the success of strategic plans. This study makes a conceptual and practical contribution to the development of strategy-based education governance, as well as encouraging the adoption of contextual and quality-oriented planning models. Implicitly, education units need to build strategic planning capacity and strengthen a reflective culture to ensure the sustainability of education reform.